การวิเคราะห์เชิงเปรียบเทียบความอยู่รอดการจัดการกลุ่มชุมชนทอผ้าไหม อำเภอบ้านด่าน จังหวัดบุรีรัมย์: Comparative Analysis of the Survival Management of the Silkworm Community Group, Ban Dan District, Buri Ram Province - แก้วขวัญไกร, ทศพร (Journal of Applied Economics and Management Strategy, 2018)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาการจัดการกลุ่มชุมชนทอผ้าไหม อำเภอบ้านด่าน จังหวัดบุรีรัมย์ 2) เปรียบเทียบการจัดการกลุ่มชุมชนทอผ้าไหม อำเภอบ้านด่าน จังหวัดบุรีรัมย์ และ 3) วิเคราะห์ความอยู่รอดการจัดการกลุ่มชุมชนทอผ้าไหม อำเภอบ้านด่าน จังหวัดบุรีรัมย์ เครื่องมือในการวิจัยได้ใช้แบบสัมภาษณ์เชิงลึกแบบกึ่งมีโครงสร้าง และแบบสัมภาษณ์กลุ่มสนทนาประเด็นเฉพาะ การวิเคราะห์ข้อมูลเกิดจากการนำข้อมูลที่ได้มาจำแนกและจัดระบบข้อมูลแบบใช้ทฤษฎี และนำมาเปรียบเทียบเหตุการณ์ของแต่ละกลุ่มชุมชนทอผ้าไหมเพื่อหาข้อสรุปเกี่ยวกับความอยู่รอดการจัดการกลุ่มชุมชนทอผ้าไหม ผลการวิจัย พบว่า การจัดการกลุ่มชุมชนทอผ้าไหม อำเภอบ้านด่าน จังหวัดบุรีรัมย์ มีองค์ประกอบวิเคราะห์ 3 มิติ กล่าวคือ มิติที่ 1 ปัจจัยนำเข้าที่ต้องอาศัยรากฐานแห่งความเข้มแข็งและการบริหารจัดการของกลุ่มชุมชนทอผ้าไหม กลุ่มที่มีจุดเด่นมิติที่ 1 มี 3 หมู่บ้าน คือ บ้านหนองแต้ ตำบลโนนขวาง บ้านสัมพันธ์ ตำบลวังเหนือ และบ้านบุ ตำบลปราสาท เนื่องจากทั้ง 3 หมู่บ้านมีการรวมกลุ่มกันในการกำหนดทิศทางของการพัฒนาอย่างเป็นประชาธิปไตย มิติที่ 2 กระบวนการผลิตที่พิจารณาด้านการเงินการลงทุนและการจัดทำบัญชี รวมทั้งด้านการผลิต พบว่าทั้ง 10 กลุ่มชุมชนทอผ้าไหมไม่มีปัญหาการผลิตหรือวัตถุดิบซึ่งสามารถหาได้ในพื้นที่ชุมชนและพื้นที่ใกล้เคียง แต่กลุ่มที่มีจุดเด่นมิติที่ 2 ในด้านการเงินการลงทุนและการจัดทำบัญชี มี 2 หมู่บ้าน คือ บ้านสัมพันธ์ ตำบลวังเหนือ และบ้านปอแดง ตำบลโนนขวาง ที่มีศักยภาพในการตรวจสุขภาพทางการเงินการลงทุนของกลุ่มอย่างเป็นรูปธรรม มีเงินสำรองไว้ใช้จ่ายในด้านต่างๆ และมิติที่ 3 ผลิตภัณฑ์ อันประกอบด้วยด้านการตลาดและด้านผลิตภัณฑ์ บรรจุภัณฑ์และฉลากสินค้า พบว่า มี 2 หมู่บ้านที่มีศักยภาพในการแข่งขันกับตลาดภายนอกที่สามารถยกระดับสินค้าให้สอดคล้องกับวัฒนธรรมร่วมสมัยในปัจจุบัน มี 2 หมู่บ้าน คือ บ้านหนองแต้ ตำบลโนนขวาง และบ้านบุ ตำบลปราสาท โดยทั้ง 2 หมู่บ้านมียอดขายสินค้าและบริการเพิ่มขึ้นทุกปี รวมทั้งมีการฉลากและบรรจุภัณฑ์เพื่อสร้างเป็นสัญลักษณ์ต่อการรับประกันสินค้า โดยสรุปการวิเคราะห์เชิงเปรียบเทียบความอยู่รอดการจัดการกลุ่มชุมชนทอผ้าไหมที่มีศักยภาพที่สามารถสร้างภูมิคุ้มกันกลุ่มได้อย่างมีประสิทธิภาพในอำเภอบ้านด่าน จังหวัดบุรีรัมย์ประกอบด้วย 3 หมู่บ้าน คือ บ้านสัมพันธ์ ตำบลวังเหนือ บ้านหนองแต้ ตำบลโนนขวาง และบ้านบุ ตำบลปราสาท This research aimed: 1) to study the management of silkworm communities in Ban Dan District, Buri Ram province; 2) to compare the management of silkworm communities in Ban Dan District, Buri Ram province; and 3) to conduct a survival analysis of the management of silkworm communities in Ban Dan District, Buri Ram province. The research tools were in-depth interviews, semi-structured interviews, and focus groups interviews which were analyzed using typology and taxonomy, as well as the comparison of the silkworm communities, in order to find a conclusion about the survival management of the silkworm community group. It was found that the management of the silkworm community in Ban Dan District could be analyzed according to three dimensions. The first dimension was “input,” based on the foundation of the strength and management of the silkworm community. Three villages related to this dimension were Nong-Tae village, Non Khwang district; Samphan village, Wang Nuea district; and Bu village, Prasat district, since all three villages were grouped together in the direction of democratic development. The second dimension was the “process” of finance and investment, accounting, and production. It was found that the 10 silkworm communities had no problem regarding production, including the raw materials that can be found in the community and in nearby areas. However, two villages related to the second dimension in terms of accounting, finance, and investment were Samphan village, Wang Nuea district; and Po Daeng village, Non Khwang district, which had the potential to clearly verify their financial and investment situation, as well as their capability to save money for spending. The last dimension was “product,” which comprised marketing and product aspects. It was found that there were two villages with the potential to compete with external markets, which can elevate their products to be in line with contemporary culture, i.e. Nong-Tae village, Non Khwang district; and Bu village, Prasat district. The goods and services of both villages have increased every year and they also employ product labeling and packaging to symbolize the warranty that they offer. In conclusion, the silkworm communities in Ban Dan District, Buri Ram Province with the potential to create an effective group immunity consist of 3 villages: Samphan village, Wang Nuea district; Nong-Tae village, Non Khwang district; and Bu village, Prasat district.